PENGARUH PENGETAHUAN INVESTASI DAN KEMAJUAN TEKNOLOGI TERHADAP KEPUTUSAN INVESTASI DENGAN MINAT INVESTASI SEBAGAI VARIABEL INTERVENING (STUDI MAHASISWA PRODI MANAJEMEN UNIVERSITAS ABDURACHMAN SALEH SITUBONDO) - Nurfadilah, Nurfadilah; Wahyuni, Ika; Subaida, Ida (Fakultas Ekonomi dan Bisnis, 2022)
The purpose of the study was to determine the effect of Investment Knowledge and Technological Advances on Investment Decisions with Investment Interest as an Intervening Variable (Student Study of Management Study Program, Abdurachman Saleh Situbondo University). The sampling technique used in this study was simple random sampling with the Slovin formula with a tolerable error rate of 10% as many as 87 people. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) Based on the research results, it is known that investment knowledge has a significant effect on investment interest, technological progress has a positive and significant effect on investment interest, investment knowledge has a positive and significant effect on investment decisions, technological advances have a positive and significant effect on investment decisions, investment interest has a positive and significant effect on investment decisions. Investment decisions, investment knowledge has a positive but not significant effect on investment decisions through investment interest, technological advances have a positive and significant effect on investment decisions through investment interest.